Mato Grosso do Sul na rota: uma análise em imagens - Ana Paula Camilo Pereira; Rafael Oliveira Fonseca; Mateus Boldrine Abrita; Daniel Amorim Souza Centuriao; Angelo Rondina Neto; angelorondina@uel.br; Rafaella Stradiotto Vignandi; Guilherme Espindola Junior (Confins)
This study analyzes the spatial segment of the Latin American Integration Network (RILA) route that crosses the state of Mato Grosso do Sul, in order to identify possible changes in territorial dynamics caused by the implementation of this road corridor, which has gradually reconfigured the territorial planning of the state, especially with regard to the logic of enabling circulation infrastructure, which sometimes conditions the speed of fluidity, sometimes shows the transformations embedded in this space.